THE IMPACT OF LYING HABITS ON STUDENT SOCIAL LIFE - Naufal Shofwan; Boby Chandra Chandra; Aulia Khalid Zaki; Azmi Fazdli Qori; Tengku Izzah Nur Machfuzi (Proceeding International Seminar of Islamic Studies, 2023)
Academic dishonesty is still common among academics, including students. This will trigger acts of corruption in the world of work later. Gunawan Ratmono said that the impact of fake news spread by perpetrators of lies can disrupt society, not only in the Maya universe but also in real life, even threatening national integrity and national stability. So, it is important for us to know that dishonesty in academia, especially students, can have fatal consequences. The purpose of this research is to see the effectiveness of official or religious self-monitoring as a strategy to reduce academic dishonesty behavior among students. Phung Marbun in Alfi Novia state that information bias in a person tends to choose and pay more attention to information that contains their opinion, meanwhile they ignore information that contradicts their opinion.through peer education. This study uses an experimental research design, namely the pretest-posttest control group design. The collection of data used in the research of this paper uses a scale of academic dishonesty, observation. The results of the study show that the official is known to be effective in reducing academic dishonesty behavior in students with an effective contribution of 47.9%. Based on these results, it can be concluded that religious self-monitoring (RESMI) through peer education is proven to reduce academic dishonesty behavior in studentsIslam as a good religion teaches its people to speak honestly, God commands people to speak honestly in the Quran. Allah SWT said in Surat At-Taubah verse 119, "O you who believe! Fear God, and be with those who are true (honest)."Rasulullah also ordered his people to tell the truth because being honest will lead to virtueThe Prophet SAW said, "You should speak honestly because honesty leads to virtue and virtue leads to heaven. And stay away from lies because lies lead to evil and evil leads to hell."Lying is a disgraceful act, it is undeniable that the habit of lying occurs and it is massive among college students. It's a shame that nowadays academic degrees and high academic levels are not accompanied by high morals, students should be pioneers, not only in matters of knowledge but also in all things. Honesty is a fixed price in life, the Qur'an forbids us to lie in many of its verses. For this reason, we are interested in exploring the negative social impacts caused by students' lying habits.